Transforming Healthcare: The Dual Impact of Artificial Intelligence on Vaccines and Patient Care - Abdul Mannan Khan Sherani; Muhammad Umer Qayyum; Murad Khan; Ashish Shiwlani; Hafiz Khawar Hussain (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Artificial intelligence (AI) has the potential to transform healthcare and immunization programs, enhance patient outcomes, and advance public health goals. This can be achieved by the incorporation of AI into these tactics. This study examines the complex effects of AI on vaccine distribution, development, efficacy tracking, personalized medicine, and fair access to healthcare. AI-driven methods speed up the development of vaccines by identifying candidates more quickly, improving the design of formulations, and making unprecedentedly accurate and fast predictions about their efficacy. Furthermore, AI improves supply chain management and vaccine distribution by streamlining scheduling, routing, and allocation procedures to provide fair access for all populations. By using AI to customize vaccination regimens based on unique traits, preferences, and risk profiles, personalized medicine techniques increase immunization efficacy and reduce side effects. In addition, AI reduces healthcare disparities by highlighting interventions for underrepresented groups, identifying underprivileged communities, reducing biases, and enhancing transparency. While AI has the potential to be a game-changer, in order to maintain moral standards and advance fair access to healthcare services, ethical issues like privacy, prejudice, transparency, and equity must be carefully considered. All things considered, the incorporation of AI into immunization programs and healthcare signifies a paradigm change that could help to mold a future in which everyone has access to more effective, equitable, and individualized healthcare.